Развитие эмоционального интеллекта как фактор управления личностным ростом - Гапон, О. Е. (ХНУРЭ, 2012)
In this paper it is considered the problem of personality growth, which arises in connection with intensive processes of individualization and globalization, taking place in modern society. Personal success depends not only on intellectual facilities, but on the personality ability such as skill to keep any situation under control, ability of self-development, creativity etc.